Ancient Mitogenomes Reveal the Domestication and Distribution of Cattle During the Longshan Culture Period in North China - Zhang, Xing; Yang, Liu; Hou, Lingyun; Li, Hua; Xiang, Hai; Zhao, Xingbo (Frontiers in Genetics, 2021)
Cattle, as an important tool for agricultural production in ancient China, have a complex history of domestication and distribution in China. Although it is generally accepted that ancient Chinese taurine cattle originated from the Near East, the explanation regarding their spread through China and whether or not this spread was associated with native aurochs during ancient times are still unclear. In this study, we obtained three nearly complete mitochondrial genomes (mitogenomes) from bovine remains dating back ca. 4,000 years at the Taosi and Guchengzhai sites in North China. For the first time at the mitogenome level, phylogenetic analyses confirmed the approximately 4,000-year-old bovines from North China as taurine cattle. All ancient cattle from both sites belonged to the T3 haplogroup, suggesting their origin from the Near East. The high affinity between ancient samples and southern Chinese taurine cattle indicated that ancient Chinese cattle had a genetic contribution to the taurine cattle of South China. A rapid decrease in the female effective population size ca. 4.65 thousand years ago (kya) and a steep increase ca. 1.99 kya occurred in Chinese taurine cattle. Overall, these results provide increasing evidence of the origin of cattle in the middle Yellow River region of China.